EXPERIMENTAL METHODOLOGY ON THE BASICS OF MULTIMEDIA IN A SCHOOL PHYSICS COURSE - Dehqonova, Ohista; Taylanov, Nizom (Физико-технологического образование, 2022)
The main task of demonstration experiments is to develop students' deep and independent knowledge of physics, independent thinking, cognition, intellectual and practical skills and competencies, including the ability to perform simple observations, measurements and experiments, use tools and materials, helps to develop the skills of analyzing the results of demonstrations, calculating measurement errors, summarizing and drawing conclusions, as well as preparing students for work. This article describes demonstration experiments based on multimedia applications for some topics in the physics course in a general secondary schools